TINJAUAN HUKUM KEDUDUKAN DAN FUNGSI NOTARIS SEBAGAI PEJABAT UMUM DALAM MEMBUAT AKTA OTENTIK (Studi Kasus di Kecamatan Bergas Kabupaten Semarang) - Umar Ma’ruf; Dony Wijaya (Jurnal Pembaharuan Hukum, 2015)
Notary is a public official assigned to represent the country and is a profession. So the notary gets trust by both government and society. The value of this trust that a notary publicly has as a general official not only because he obtained because of the law in making an authentic deed. This study uses empirical juridical approach, which is a method used to solve problems by first researching the primary data in the field and then followed by a study of secondary data available.The result of the research states that 1) the function of the notary as a public official is to make an authentic deed of all acts, agreements and statutes required by laws and regulations as well as a notary authorized to validate the signature and specify the date of the letter under the hand by registering in a special book , To record the letters under his / her hand by registering in a special book, to make copies of the original letters under the hand in the form of copies containing the description as written and described in the corresponding letter, endorsing matches and photocopies with the original letter, 2) Efforts Preventive measures that can be made by a notary in making authentic deed so that no mistake occurs in the exercise of its authority of making an authentic deed, the notary must make the deed in accordance with the forms and ordinances established by law.